2004
DOI: 10.1111/j.1365-2958.2004.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the Pasteurella multocida toxin translocation domain

Abstract: SummaryThe Pasteurella multocida toxin (PMT) is a potent mitogen which enters the cytosol of eukaryotic cells via a low pH membrane translocation event. In common with the Escherichia coli cytotoxic necrotizing factor 1 (CNF1), the core of the PMT translocation domain is composed of two predicted hydrophobic helices (H1 -residues 402-423, H2 -437-457) linked by a hydrophilic loop (PMT-TL -424-436). The peptide loop contains three acidic residues (D425, D431 and E434), which may play a role equivalent to D373, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…Translocation of PMT-DTa into the cytosol depends on acidification of the endosome, as revealed by inhibition of EF-2 ADP-ribosylation by PMT-DTa upon treatment with an inhibitor of vacuolar H ϩ -ATPase (47). This is in congruence to previous findings that the biological effect of PMT depends on acidification during uptake (11,21). To follow intracellular trafficking, PMTDTa was labeled site specifically at the N terminus with a fluorescent epitope.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Translocation of PMT-DTa into the cytosol depends on acidification of the endosome, as revealed by inhibition of EF-2 ADP-ribosylation by PMT-DTa upon treatment with an inhibitor of vacuolar H ϩ -ATPase (47). This is in congruence to previous findings that the biological effect of PMT depends on acidification during uptake (11,21). To follow intracellular trafficking, PMTDTa was labeled site specifically at the N terminus with a fluorescent epitope.…”
Section: Discussionsupporting
confidence: 58%
“…The receptor binding and translocation domains are located in the N terminus (aa 1 to 574). Whereas the receptor binding domain has not been characterized in detail, two amphipathic helices, covering residues 402 to 457, are suggested to be involved in membrane insertion and translocation (21). So far, the cell surface receptor of PMT is not known (22).…”
mentioning
confidence: 99%
“…Thus, we consider that C-PMT represents the intracellularly active moiety of the toxin. This does not conflict with the fact that the membrane translocation domain is reportedly composed of regions spanning residues 402-457 (14). Furthermore, the receptor-binding domain could be located on the N-terminal side of the translocation domain.…”
Section: Discussionmentioning
confidence: 42%
“…Previous reports have shown that PMT binds to an unknown receptor on target cells, is internalized by endocytosis, and escapes from the acidic endosome into the cytoplasm. The N-terminal region of the toxin is believed to mediate these procedures (14,17). We hypothesize about the subsequent action of PMT as follows: Although it is unknown whether the Nterminal region is clipped off when the toxin molecule enters the cytoplasm, the C-terminal region, at least, corresponding to C-PMT, is transferred to the vicinity of the plasma membrane with the aid of the C1 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation